The Irish time : challenges and strategies - Angga Erlangga (2010)
The objective of the study is to understand the Business and Cultural Challenges to The Irish Times as a major printed media player in the Republic of Ireland, as well as to get insights on the successful strategies that it has and will employ to develop and grow. The Cultural Universals, Communication and Cultural Values of Ireland are first reviewed to provide a rich context for the examination of The Irish Times' key challenges and strategies. From Secondary Case Analysis, it is assessed that there are four key challenges that The Irish Times needs to address to stay competitive. The challenges of Fierce Local Competition and Small International Circulation are predominatly issues of increasing readershp. The challenges of Erosive Substitues (Online Media) and New Entrants, and New Generation Readers are largely issues of dealing with new trends. To address these challenges, The Irish Times is observed to focus on two strategic thrusts: a set of sound business strategies and an effective organization to execute them. Three key business strategies are identified. First, The Irish Times is observed to adopt a Shield and Strike business strategy to increase its readership. The Irish Times has shielded its traditional stronghold of ABC1 readers by maintaining itself as the leading quality newspaper in Ireland. In parallel, it has launched supplementary products with the newspaper to enhance its appeal to other categories of readers. Second, The Irish Times has diversified its operations. Instead of trying to beat the challenges posed by new genres of newspaper (new entrants) and online media (substitute) with the The Irish Times itself, the company has joined them and launched new products to capture the new markets. Third, The Irish Times has continued its efforts to keep up with the Information Age, so that it could better - engage the new generation readers in their preferred platforms (Be Geek) at their pace (Be Quick). The Irish Times recognised that each business strategy would require dedicated resources and people. To effectively execute the business strategies and yet remain profitable, The Irish Times has strived to keep its organization lean and fit. This ensures productive is high while cost is low.